Translation and Validity of the Malay Version of the Five-Factor Nonverbal Personality Questionnaire (FFNPQ) - Ab Rashid, NF; Arifin, WN; Kueh, YC; Yusoff, N (IIUM Medical Journal Malaysia, 2020)
Introduction: The Five-Factor Nonverbal Personality Questionnaire (FF-NPQ) is a non-verbal personality inventory consisting of illustrations of different social situations, designed to measure five broad factors underlying the Big-Five model of personality. This study aimed to prove the validity of the FF-NPQ in Malaysia. Methods: The FF-NPQ instruction and the answer option were translated to the Malay language, which is the main language spoken in Malaysia. A total of 153 university students aged 18–30 years from Universiti Sains Malaysia were involved in this study. Confirmatory factor analysis (CFA), composite reliability and intraclass correlation (ICC) were applied to show evidence of validity by internal structure. Results: CFA indicated that only 26 out of 60 items remained in the final model while maintaining the five personality factors. Each factor had a good composite reliability value of 0.68–0.77. The ICC values from the test-retest analysis ranged from 0.65 to 0.75. Conclusion: Overall, the shortened Malay Version of the FF -NPQ (five-factor, 26 items) exhibited acceptable evidence of validity in Malaysia.